Erythrocytes – unique model of the organism’s adaptation capabilities - Garkava, Kateryna (Problems of Environmental Biotechnology, 2021)
The special structure of erythrocytes and the condition of their membranes in human body allows to make a judgement of the adaptive capabilities of the organism.